Peningkatan Hasil Belajar IPAS Menggunakan Model Project Based Learning di Kelas IV SD Negeri 51 Sungai Jaring - Desya Nurhilsa Alvianti; Masniladevi Masniladevi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2025)
This research was motivated by the low natural and social science learning outcomes of fifth grade students at SDN 52 Sungai Jaring. This study aims to describe the improvement of student learning outcomes in IPAS learning using the Project Based Learning model in grade IV SD. This research is a classroom action research that uses quantitative and qualitative approaches through four stages of implementation, namely: planning, implementation, observation and reflection carried out for 2 cycles. The subjects of this study were all fourth-grade students of SD Negeri 51 Sungai Jaring, totalling 16 people. The results showed the teaching Module assessment in cycle I was obtained with an average of 81.24% (B) and increased in cycle II to 91.66% (SB). Teacher activity assessment in cycle I was obtained with an average of 82.81% (B) increasing in cycle II to 93.75% (SB). Assessment of learner activities in cycle I averaged 82.24% (B), increasing in cycle II to 93.37% (SB). The learning outcomes of students in cycle I obtained an average of 77.34 with qualifications (B), increasing in cycle II to 84.68 with qualifications (B). Thus, it can be concluded that the project-based learning model can improve IPAS learning outcomes in class IV SD Negeri 51 Sungai Jaring.